Tingkat Pengetahuan dan Sikap terhadap Kesehatan Reproduksi Remaja antara Kelompok Orang Tua dan Kelompok Remaja - Vina Viskayuli Vrihat; Hartiah Haroen; Raini Diah Susanti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to identify differences in the level of knowledge about adolescent reproductive health and attitudes toward adolescent reproductive health between adolescents and their parents. This research method is quantitative and descriptive, using a cross-sectional approach. The results showed that, in general, almost half of the two groups had sufficient knowledge, teenagers (39.5%) and parents (38.2%), then more parents (55.3%) had a supportive attitude towards health. reproduction of adolescents adolescents compared to adolescents (50%). In conclusion, the level of knowledge about adolescent reproductive health and attitudes towards adolescent reproductive health in adolescents and parents of adolescents in RW X Sukamentri Village, Garut District, City, Garut Regency is the same. Keywords: Reproductive Health, Parents, Knowledge, Adolescents, Attitudes